2019
DOI: 10.7759/cureus.3821
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Bradycardia and QT Interval Prolongation in West Nile Virus Encephalitis: A Case Report

Abstract: Cardiac arrhythmias were reported in cases of West Nile Virus (WNV) encephalitis; however, the underlying pathophysiology remains incompletely understood. We present a 67-year-old male with altered mental status, later diagnosed with WNV encephalitis. Hospital course was complicated by progressive sinus bradycardia and corrected QT (QTc) prolongation. These findings persisted despite the absence of classical causes and resolved only after improvement of the underlying encephalitis. After excluding classical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Other viruses have also been associated with QTc prolongation, including HIV, 13 HCV coinfection, 14 and West Nile virus. 15 HIV-associated inflammation, specifically elevated IL-6 level, is further independently associated with QT prolongation 23 and prolonged repolarization represented as T wave onset-to-peak duration. 24 Infection with SARS-CoV-2 may result in cardiac enzyme release, which parallels the systemic inflammatory response marked by elevation of ferritin, LDH, CRP, and IL-6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other viruses have also been associated with QTc prolongation, including HIV, 13 HCV coinfection, 14 and West Nile virus. 15 HIV-associated inflammation, specifically elevated IL-6 level, is further independently associated with QT prolongation 23 and prolonged repolarization represented as T wave onset-to-peak duration. 24 Infection with SARS-CoV-2 may result in cardiac enzyme release, which parallels the systemic inflammatory response marked by elevation of ferritin, LDH, CRP, and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Specific viruses are also associated with QTc prolongation. 13 , 14 , 15 Few analyses have compared QTc intervals between patients with and without COVID-19, an inflammatory viral condition. The present study used multivariable models to investigate which clinical characteristics were associated with prolonged QTc from baseline in patients with COVID-19 and to isolate the independent association of COVID-19 infection with QTc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strikingly high prevalence of sinus bradycardia amongst COVID-19 survivors in the present study, contrasts with other respiratory viral infections such as influenza. Profound sinus bradycardia or sinus asystole leading to syncope have only been rarely reported in other viral infections including influenza [23], herpes simplex virus [24,25], Ebola and West Nile virus [26,27], attributed to acute myocarditis or autonomic nervous system involvement. In the outbreak of SARS due to SARS-CoV in 2003, studies from Canada and Hong Kong have also reported high prevalence of sinus bradycardia in hospitalized SARS patients as high as 27.5% [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…As we know, some viruses (eg human immunodeficiency virus, hepatitis C virus and West Nile virus) are associated with QTc interval prolongation 14‐16 . However, the relationship between QTc prolongation and SAR‐CoV‐2 infection remains uncertain.…”
Section: Case Descriptionmentioning
confidence: 99%